Comparison of procedures based upon Rappaport-Vassiliadis medium with those using Muller-Kauffmann medium containing Teepol for the isolation of Salmonella sp. - Vassiliadis, P. (Cambridge University Press, 1987)
A total of 308 samples of different types were examined for the presence of salmonellas by means of three different procedures. The first consisted of pre-enrichment in buffered peptone water followed by enrichment in Rappaport-Vassiliadis medium (P/RV). The second differed only in that 1% Teepol was added to the pre-enrichment medium (PT/RV). In the third, buffered peptone water with 1% Teepol was followed by enrichment in Muller-Kauffmann tetrathionate broth also containing 1% Teepol (PT/MKT). The first of these combinations (P/RV) proved superior to the others both in terms of isolation rates and in the appearance of suspicious colonies.